2015
DOI: 10.1108/ijchm-03-2014-0150
|View full text |Cite
|
Sign up to set email alerts
|

Types of organizational innovativeness and success in Austrian hotels

Abstract: Purpose – The purpose of this paper is to identify different types of organizational innovativeness in Austrian hotels and analyze their connection to (innovation) success. In the face of growing international competition, innovation is becoming increasingly important for Austria’s hotel industry. A prerequisite for innovation is organizational innovativeness. Design/methodology/approach – This paper is based on a quantitative survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Firms armed with innovativeness capabilities can reap the associated benefits, such as improved and new products and services, thereby leading to enhanced performance (Dibrell et al, 2014). Several studies in the tourism sector confirm the connection between firm's innovativeness and its performance indications (Gomezelj, 2016;Kessler et al, 2015). Using data from SMEs in the tourism sector, researchers have demonstrated that there is a positive association between innovation in products and processes and financial performance (Martínez-Román et al, 2015).…”
Section: Organizational Capabilities and Planning Effectivenessmentioning
confidence: 99%
“…Firms armed with innovativeness capabilities can reap the associated benefits, such as improved and new products and services, thereby leading to enhanced performance (Dibrell et al, 2014). Several studies in the tourism sector confirm the connection between firm's innovativeness and its performance indications (Gomezelj, 2016;Kessler et al, 2015). Using data from SMEs in the tourism sector, researchers have demonstrated that there is a positive association between innovation in products and processes and financial performance (Martínez-Román et al, 2015).…”
Section: Organizational Capabilities and Planning Effectivenessmentioning
confidence: 99%
“…The first question refers to types of innovation commonly differentiated as product, process, marketing and organizational innovation (OECD, 2005;Schumpeter, 1934); the second differentiates between incremental (significant improvement) from radical (completely new) innovations (Schumpeter, 1934) while the third distinguishes new to the world from new to the unit of observation/company innovation (Sørensen, 2004). Besides newness, another key aspect of innovation is implementation (Kessler et al, 2015) as innovation only occurs when products/services, processes, marketing methods and organizational measures are put to use in organization's operations (OECD, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovation is generally perceived as one of the key drivers of development and competitiveness (Griesmann et al, 2013;Kessler et al, 2015) and is recognized as a source of increased competitiveness for tourism products, firms and destinations (Hall and Williams, 2008;Hall, 2009). However, tourism businesses have significant difficulties in 'protecting' their innovations as it is usually rather easy for competitors to copy new successful ideas (Camisón and Monfort-Mir, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, contemporary literature synthesis indicates that there is still a theoretical disjunction as to the exact role of religion within this process. Further, if and why it (religion) is specifically linked to the many forms of perceived business success (Dai, 2012;Kessler, Pachucki, Stummer, Mair, & Binder, 2015;Lock, 2010;Tervonen & Haapasalo, 2012) and the role it plays within any other process in which it exists as an element. Moreover, in its practical usage, generalist interpretation ~ of knowledge ~ does not automatically indicate full significance of the knowledge content nor its transfer or absorptive capability.…”
Section: Business Based Knowledge Overviewmentioning
confidence: 99%